Strategi Kebijakan Pembangunan Ekonomi Dalam Perspektif Islam (Studi Kritis Terhadap Pemikiran Ekonomi Neo Klasik) - Arie Rachmat Soenjoto (University of Darussalam Gontor, 2018)
Liberalization and deregulation which are at the core of Neo-Classical economic policy have led developing countries to the brink of poverty. Although economic growth has increased but the problem of equity and fulfillment of basic needs cannot be overcome, this can be seen in Indonesia as one of the users of Neo-Classical policies. According to data from the statistics center in March 2017 the number of poor people reached 27.77 million people. Maluku and Papua have been named as the regions with the highest percentage of poor people, namely 24.14% of the total population of Indonesia. This figure is the highest percentage of poverty in Indonesia. Even though Papua is an Indonesian gold barn. In 2011, Indonesia’s Gini ratio reached 0.41, meaning that the level of inequality in Indonesia is quite high. This indicates the failure of Neo-Classical policies in building the economy. This research was conducted to fi nd out how Neo-Classical economic policies and Islamic economics in economic development, as well as to fi nd out the views of Islam on Neo-Classical economic policies in economic development. Research research library is a study of criticism using books as a source of research, and using descriptive-analytical methods that provide an overview of Neo-Classical policies with an analysis of Islamic perspectives. Primary data of Adam Smith’s thinking from the literature of books, journals, papers, magazines and articles. Secondary data from the thoughts of Islamic economists from the literature of books, journals, papers and articles. The results of the analysis of this study can be seen that Islam has elements of interconnected strategies that can achieve economic development goals, namely the mechanism of moral fi ltering, correct motivation, socio-economic restructuring, fi nance, and the role of the State. Five policy actions include human resource development, wealth equity, economic restructuring, fi nancial restructuring, and strategic policy planning. In the Islamic perspective, liberalization is recognized but has social responsibility, while deregulation means anti-government. In Islam the government must be responsible for fulfilling 5 sharia objectives. In implementing development policies and strategies, the government is expected to be able to instill Islamic values in every economic activity by creating a healthy socio-economic without disturbing individual rights and motivating the community with this maqashid sharia will be achieved.